Integrating Blue-Green Infrastructure strategies to enhance climate resilience in Colombia. - Medina Rivera, Laura; Faggian, Robert (European Journal of Sustainable Development, 2024)
Colombia is a tropical developing country that faces frequent and unpredictable flood events. Previous efforts to mitigate the impacts of flood have revolved around traditional approaches like the construction of levees. However, as seen in other parts of the world, levees often make flooding worse. Considering the increasing frequency and severity of extreme weather associated with a changing climate, it is clear there is a pressing need for more effective strategies to mitigate the impacts of extreme weather events. However, poor data availability makes understanding flood risk and developing new approaches a difficult task. This research examines the feasibility of Blue-Green Infrastructure (BGI) as a nature-based methodological approach to deal with flooding focuses, focusing on the Guarapas River and Pitalito town, in regional Colombia. Utilizing PCSWMM as a modelling tool, the study demonstrates the applicability of BGI in reducing peak flow. Validating the model proved difficult given the substantial gaps in official data sources. So, it was necessary to use proxies such as social media posts of flood events, to determine the date and severity of flood events in the town. The analysis revealed that deploying a limited number of BGI elements can mitigate the adverse effects of floods in a cost-effective manner, and that the underpinning modelling could be carried out using data proxies such as local news reports and social media posts. This research contributes to the growing body of knowledge on BGI as a valuable solution for flood management in a changing climate but does so in a developing country context. By showcasing the feasibility of BGI in reducing peak flow and enhancing resilience in a region with limited data resources, this study shows that it is possible for developing countries to move away from traditional and sometimes increasingly ineffective solution. Barriers to adoption are still significant. But nature-based solutions to flooding represent a new, proactive measure in addressing the challenges posed by climate change, with implications for policymakers and stakeholders involved in sustainable planning.